2022
DOI: 10.3390/universe8050262
|View full text |Cite
|
Sign up to set email alerts
|

Weak Deflection Angle and Greybody Bound of Magnetized Regular Black Hole

Abstract: In this paper, we examine the weak deflection angle and greybody bound for a magnetized regular black hole. For this purpose, we apply the Gauss–Bonnet theorem on the black hole and obtain the deflection angle in plasma and non-plasma mediums. Moreover, we investigate graphically the effect of impact parameter on the deflection angle for regular black hole in both mediums. We examine that the deflection angle goes to infinity when the impact parameter approaches zero. We also observe that the deflection angle … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In another work, the weak deflection angle by black holes and wormholes has been extensively studied with different examples and wormhole structures [60]. Apart from these, there are several studies dealing with deflection angle in the domain of black holes and wormholes [61][62][63][64][65]. Traversable wormholes in extended teleparallel gravity with matter coupling is studied in ref.…”
Section: Introductionmentioning
confidence: 99%
“…In another work, the weak deflection angle by black holes and wormholes has been extensively studied with different examples and wormhole structures [60]. Apart from these, there are several studies dealing with deflection angle in the domain of black holes and wormholes [61][62][63][64][65]. Traversable wormholes in extended teleparallel gravity with matter coupling is studied in ref.…”
Section: Introductionmentioning
confidence: 99%
“…Sanchez showed that the absorption spectrum as a function of the frequency makes clear oscillations characteristic of a diffraction pattern, where the oscillations occur around the constant value of the geometrical optics with decreasing amplitude and constant period. The absorption cross-section for black holes have been studied in literature for a various black hole spacetimes [46,104,[129][130][131][132][133][134][135][136][137][138][139][140], especially for the low-frequency behavior of the absorption and for the zero-frequency limit (it becomes equal to surface area of the black hole horizon) [130,141,142], as well as the high-frequency behavior of the scalar absorption via Sinc approximation [128,143,144].…”
Section: Introductionmentioning
confidence: 99%